Nature's place in Hegel's system (Is the truth, temporal?) - Muhammad Chawoushi (حکمت اسرا, 2018)
In the last section of "knowledge of logic", the absolute idea is spoken. In his history of philosophy, Shilling considers the absolute part of Hegel's scientific system to discuss God in the degree of inwardness. Moving from each category to another, although it is Becoming, at sametime is the fertilize of concepts and their leading to absolute idea. Hence, the transition from logic to nature is Reminder of the same Famous question that how God's step to the nature? The importance of nature place in Hegel's philosophy lies in this question. On the other hand, the important character of negativity, the only stimulant of the Hegelian system, appears more clearly in the process of passing through logic to nature.